Emergencies and the limits of legality - Ramraj, Victor Vridar, 1968- (Cambridge University Press, 2008)
Most modern states turn swiftly to law in an emergency. The global response to the 11 September 2001 attacks on the United States was no exception, and the wave of legislative responses is well documented. Yet there is an ever-present danger, borne out by historical and contemporary events, that even the most well-meaning executive, armed with extraordinary powers, will abuse them. This inevitably leads to another common tendency in an emergency, to invoke law not only to empower the state but also in a bid to constrain it. Can law constrain the emergency state or must the state at times act outside the law when its existence is threatened? If it must act outside the law, is such conduct necessarily fatal to aspirations of legality? This collection of essays - at the intersection of legal, political and social theory and practice - explores law's capacity to constrain state power in times of crisis.